A "direct five-step procedure" for the preliminary seismic design of buildings with added viscous dampers. (15th October 2018) - Palermo, Michele; Silvestri, Stefano; Landi, Luca; Gasparini, Giada; Trombetti, Tomaso
Highlights: Direct procedure for preliminary seismic design of structures with added dampers. Based on the "five-step procedure" originally developed in 2010. Procedure applicable to yielding structures with inter-storey viscous dampers. Sizing of viscous dampers and structural elements with two equivalent static analyses. Numerical verification carried out by means of two applicative examples. Abstract: In the present work a direct procedure for the preliminary seismic design of building structures with added dampers is described which represents the simplification of the so-called "five-step procedure" originally developed in 2010 by some of the authors. The procedure is applicable to yielding frame structures with a generic along-the-height distribution of inter-storey viscous dampers. It is aimed at guiding the structural engineer through the sizing of both viscous dampers and structural elements making use of an equivalent static analysis approach. First, the peak structural response under earthquake excitation is reduced by imposing an overall reduction factor accounting for both the ductility demand and the viscous damping provided by the added dampers. Second, linear damping coefficients are calculated in order to reduce the structural response according to the selected target damping ratio. Then, analytical formulas allow the estimation of peak velocities and forces in the dissipative devices, and an energy criterion is used to identify the non-linear mechanical characteristics of the actual manufactured viscous dampers. Finally, the internal actions in the structural elements are estimated through the envelope of two equivalent static analyses (ESA). At this initial stage of the research, the procedure appears suitable for the preliminary design phase, while correction factors for the higher modes contributions need to be applied to improve its accuracy, especially for high-rise buildings. A numerical verification of the final behaviour of the system by means of non-linear time-history analyses is recommended. An applicative example is finally developed to highlight the soundness of the procedure.